Genetic characterisation of adult primary pleomorphic uterine rhabdomyosarcoma and comparison with uterine carcinosarcoma. Issue 2 (19th April 2021) - Ashley, Charles W; Da Cruz Paula, Arnaud; Ferrando, Lorenzo; Gularte‐Mérida, Rodrigo; Sebastiao, Ana P M; Brown, David N; Gazzo, Andrea M; Pareja, Fresia; Stylianou, Anthe; Abu‐Rustum, Nadeem R; Reis‐Filho, Jorge S; Buehler, Darya; et al.
Abstract : Aims: To characterise the genetic alterations in adult primary uterine rhabdomyosarcomas (uRMSs) and to investigate whether these tumours are genetically distinct from uterine carcinosarcomas (UCSs). Methods and results: Three tumours originally diagnosed as primary adult pleomorphic uRMS were subjected to massively parallel sequencing targeting 468 cancer‐related genes and RNA‐sequencing. Mutational profiles were compared with those of UCSs ( n = 57) obtained from The Cancer Genome Atlas. Sequencing data analyses were performed using validated bioinformatic approaches. Pathogenic TP53 mutations and high levels of genomic instability were detected in the three cases. uRMS1 harboured a likely pathogenic YTHDF2 – FOXR1 fusion. uRMS2 harboured a PPP2R1A hotspot mutation and amplification of multiple genes, including WHSC1L1, FGFR1, MDM2, and CCNE1, whereas uRMS3 harboured an FBXW7 hotspot mutation and an ANKRD11 homozygous deletion. Hierarchical clustering of somatic mutations and copy number alterations revealed that these tumours initially diagnosed as pleomorphic uRMSs and UCSs were similar. Subsequent comprehensive pathological re‐review of the three uRMSs revealed previously unidentified minute pan‐cytokeratin‐positive atypical glands in one case (uRMS3), favouring its reclassification as UCS with extensive rhabdomyosarcomatous overgrowth. Conclusions: Adult pleomorphic uRMSs harbour TP53 mutations and high levels of copy number alterations. Our findings underscore the challenge in discriminating between uRMS and UCS with rhabdomyosarcomatous differentiation. Abstract :